Implementasi Pembelajaran Aqidah Akhlak Dalam Pembentukan Karakter Tanggung Jawab Pada Siswa Kelas VII Di MTs Unggulan Sabilillah Lamongan - ., Arwani; Ashrofun Nashr, M. Naqouib (Jurnal Murid, 2026)
One of the subjects that contributes to shaping students' character is the subject of Aqidah Akhlak. In the learning process, students are not only expected to understand theoretically but are also directed to implement it in their daily lives. Initial observations by the researcher at MTs Unggulan Sabilillah Lamongan show that some seventh-grade students exhibit a lack of responsibility. This study aims to determine how the Aqidah Akhlak learning is implemented and its influence on the formation of students' responsible character. The research method used is descriptive qualitative. The results of the study indicate that the Aqidah Akhlak learning supports the formation of students' responsible character, even though there are several inhibiting factors in its implementation.